Myth and materiality in a woman's world : Shetland 1800-2000 - Abrams, Lynn (Gender in history., 2005)
Shetland has a history unique in Europe, for over the past two centuries it was a place where women dominated the family, economy, and the cultural imagination. Women ran households and crofts without men. They maintained families and communities because men were absent. And they constructed in their minds an identity of themselves as 'liberated' long before organised feminism was invented. And yet, Shetland is a place which was made by the most masculine of societies - those of the Picts, Scots and above all the Vikings - and its contemporary identity still draws on the heroic exploits and sa.